Thermal property characterization of chitin from Leucaena Leucocephala extraction / Shareena Shahira Tajul Arus - Tajul Arus, Shareena Shahira (2017)
Thermal property characterization of chitin from Leucaena Leucocephala (LL) extraction is obtained by using themagravimetric analysis (TGA) and Elemental Analyzer. The purposes of this research were to characterize chitin by extraction of LL pod with 6M HCL by using Thermagravimetric Analysis (TGA) and Elemental Analyzer. By using the equipments, the thermal property can be determined. The samples are prepared by chemical process, which are extraction of chitin using 6M HCl and neutralization using 12M NaOH . The prepared samples then will be test for the thermal property by the TGA and Elemental Analyzer.